PERAN MEDIA SOSIAL SEBAGAI PEMASARAN DIGITAL BAGI UMKM - Nia Rifanda Putri; Wanda Laksniyunita; Kherayani Nur; Basnendar Herry Prilosadoso; Yovita Yulia M. Zai (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to determine the role of social media as digital marketing for MSMEs. This research approach collects data through literature studies, which involve reading literature from various sources including books, articles, journals and reports using qualitative and deductive approaches. The findings in this study are that there are several types of social media that can be used by MSME actors as digital marketing tools, namely blogs, microblogs, video-sharing sites, picture-sharing sites, and social networking sites. Then there is also the role of social media as a digital marketing tool for MSMEs, including social media can build brand awareness, social media as a means of finding potential buyers, social media can build closeness with consumers, social media is one of the effective and direct promotional media to the target, and social media can dig up information from consumers and potential consumers.